A pair of chiral flavonolignans as novel anti‐cyanobacterial allelochemicals derived from barley straw (Hordeum vulgare): characterization and comparison of their anti‐cyanobacterial activities. (27th August 2013) - Xiao, Xi; Huang, Haomin; Ge, Zhiwei; Rounge, Trine B.; Shi, Jiyan; Xu, Xinhua; Li, Ruobing; Chen, Yingxu
Summary The inhibitory effect of barley straw (Hordeum vulgare) on cyanobacteria has been observed in many field and laboratory studies for over 30 years, although the compounds responsible for this anti‐cyanobacterial effect have remained unknown. In this study, a pair of chiral flavonolignans were isolated from barley straw extract using a bioassay‐guided isolation procedure against Microcystis sp. The structures of the allelopathic compounds were elucidated by NMR (nuclear magnetic resonance) and HPLC‐MS (high performance liquid chromatography‐mass spectrometry), and turned out to be salcolin A and B. The enantiomers differ in their anti‐cyanobacterial abilities. Both enantiomers exhibited inhibitory effects on Microcystis sp., and the EC50 (concentration for 50% of maximal effect) of salcolin A and B were 6.02 × 10−5 and 9.60 × 10−5 mol l−1, respectively. Furthermore, the modes of actions of the enantiomers were investigated and compared at a single cell level by flow cytometry. Salcolin A was found to induce an increase on cyanobacterial intracellular ROS (reactive oxygen species) levels and to inhibit esterase activity, whereas salcolin B caused leakages of cyanobacterial cytoplasms. Thus, salcolin A was more 'algistatic', and salcolin B was more 'algicidal'. This study suggests that salcolin is the key allelochemical in barley straw's inhibitory effect on cyanobacteria and could be used as an agent in the future control of cyanobacterial harmful algae blooms.